2017
DOI: 10.1017/cts.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

IRB Process Improvements: A Machine Learning Analysis

Abstract: ObjectiveClinical research involving humans is critically important, but it is a lengthy and expensive process. Most studies require institutional review board (IRB) approval. Our objective is to identify predictors of delays or accelerations in the IRB review process and apply this knowledge to inform process change in an effort to improve IRB efficiency, transparency, consistency and communication.MethodsWe analyzed timelines of protocol submissions to determine protocol or IRB characteristics associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The highly skewed right-sided tail is composed of statistically significant "outliers" identified using Tukey one-sided test (p = 0.0001). Further analyzing outliers creates an opportunity to identify variations affecting performance that might benefit from a change in the workflow [28][29][30][31]. Outliers were independently identified for 2 key phases of the approval process: (1) administrative review by staff; and (2) IRB committee review (see below).…”
Section: Time Required For Irb Approvalmentioning
confidence: 99%
“…The highly skewed right-sided tail is composed of statistically significant "outliers" identified using Tukey one-sided test (p = 0.0001). Further analyzing outliers creates an opportunity to identify variations affecting performance that might benefit from a change in the workflow [28][29][30][31]. Outliers were independently identified for 2 key phases of the approval process: (1) administrative review by staff; and (2) IRB committee review (see below).…”
Section: Time Required For Irb Approvalmentioning
confidence: 99%
“…The second aspect was limited staffing, which could be addressed by automating processes within that system that were historically performed manually. It is shown that the ‘human factor’ plays a large role in IRB processing time so automation will help to reduce staff impact [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that scholars understand the ethical requirements for studies involving human participants and consider them as highly relevant. Still, they emphasize that the process is usually too long and restrictive (Shoenbill et al, 2017). Since institutional regulations frequently change, researchers involved in socially engaged arts-related projects and other researchers often experience difficulties through this process (Dingwall, 2008(Dingwall, , 2012Emmerich, 2013;Librett & Perrone, 2010;Lombardo, 2017).…”
Section: Introductionmentioning
confidence: 99%